Constellations of mobility: The politics of dream-making - Ahmed, Yara (AUC Knowledge Fountain, 2019)
This thesis is concerned with how we navigate the labyrinthine nature of our lifeworlds; as we build futures, we dream of other time-spaces. We hope; we wait; we feel stuck. More particularly, this thesis is concerned with the processes of movement that occur when precarious queer bodies dream of a somewhere else, echoing what is brewing in the body, what spills over the boundaries and categories of the possible and the impossible. I take an ethnographic approach in an attempt to trace the multiple projects of dream-making that are becoming around my interlocutors. These projects translate to a crafting of paths that navigate the tensions of moving out of a parent’s house, confessing an infatuation, getting out of bed in the morning, and imagining that life is elsewhere, can be otherwise. As bodies cultivate attachments amidst a colossal of heavy objects, they are often infested with uncertainty, fear, a constant diverging from one site to the next. They attach themselves to one object of desire and detach themselves from another. This temporary being in one world then the next, a constant searching for the somewhere else, reflects a complex relationship with hope, desire, fear, helplessness, stillness, depression, and frustration. Dream-making in my analysis is a site of temporal and spatial constructions. In this thesis, I investigate the architecture that surrounds dreaming of a better life and explore its sociopolitical implications and its incarnation in the everyday. The kind of architecture I am referring to here does not have a blueprint; however, it is endlessly shifting and changing. In taking a spatio-temporal approach to these questions, I am hoping to open up the borders of inquiry and rethink time-space through dream-making projects of the imagination for a more nuanced understanding of movement.